Докажите тождество a(b+c)² + b(c+a)² + c(a+b)² — 4abc = (a+b)(b+c)(c+a)

  • решаем слева: a(b^2+2ab+c^2)+b(c^2+2ac+a^2)+C(a^2+2ab+b^2)-4abc=ab^2+2ab+ac^2+bc^2+2abc+a^2b+a^2c+2abc+b^2c-4abc=ab^2+ac^2+bc^2+a^2b+a^2c+b^2c+2abc

    теперь правую часть:2abc+ac^2+b^2c++bc^2+a^2b+a^2c+b^2a решая дальше получим 0=0

  • a(b+c) + b(c+a) + c(a+b) — 4abc = (a+b)(b+c)(c+a)

    a(b+2bc+c)+b(c+2ca+a)+c(a+2ab+b)-4abc=(ab+ac+b+bc)(c+a)

    ab+2abc+ac+bc+2abc+ab+ac+2abc+bc-4abc=abc+ab+ac+ac+bc+ab+bc+abc

    (2abc+2abc+2abc-4abc)+ab+ac+bc+ab+ac+bc=(abc+abc)+ab+ac+ac+bc+ab+bc

    2abc+ab+ac+bc+ab+ac+bc=2abc+ab+ac+ac+bc+ab+bc

    доказано


  • Добавить комментарий

    *
    *

    Required fields are marked *